Impact of clinical pharmacist intervention on diabetes related quality-of-life in an ambulatory care clinic - Elinor CG. Chumney (Pharmacy Practice, 2007)
The purpose of this one-year observational studywas to evaluate quality of life in patients at theMedical University of South Carolina FamilyMedicine clinic who were followed by a clinicalpharmacist diabetes educator.Methods: Patients who have been seen by theclinical pharmacist for diabetes education andmanagement services were contacted by telephoneand asked to complete a previously validatedDiabetes-related Quality of Life (DRQL) survey. Inaddition, the patients most recent hemoglobin A1C,blood pressure, fasting lipid panel and aspirin usewere obtained from the electronic medical record.Correlation and logistic regression analysis wascompleted in order to assess the quality of life scoreand clinical outcomes.Results: A total of 47 patients completed the survey(37%). The median overall score was 1 (1-verysatisfied; 5-very dissatisfied). Patients who weremore satisfied with their current treatment tended tohave lower LDL, systolic and diastolic bloodpressure (BP) values (r=0.32, 0.3, 0.33; p=0.03,0.03, 0.02). In addition, patients taking moremedications were more dissatisfied with the amountof time spent managing their disease (r=0.29,p=0.04), felt more pain associated with thetreatment of their disease (r=0.32, p=0.02), andwere more worried that their body looked differentas a result of their diabetes (r=0.32, p=0.02).Conclusion: Patients in this clinic were highlysatisfied with their quality of life. The authors foundthat trends exist for relationships between severalimportant clinical parameters and quality of life.